Effects of Simulated Low Vision on Postural Adjustment to Changes in Center of Mass in Older Adults. Issue 2 (3rd April 2017) - Copolillo, Al; Christopher, Ann; Lyons, Amanda
ABSTRACT: This study examined how instrumental activities of daily living (IADL) performed by older adults under low-vision simulation conditions affect postural adjustments to changes in center of mass (COM). Ten participants with normal vision performed seven activities under two conditions, normal vision, and simulated macular degeneration (MD). Postural adjustment to changes in COM and time to complete activities were recorded. Low vision was compared to normal vision using Wilcoxon signed rank and t tests. Differences between the two conditions were statistically significant for postural adjustments to change in COM and time. Postural adjustments and time to perform IADLs are greater under simulated low vision conditions versus normal vision. These preliminary findings support research with older adults with MD, who may be at risk when making movement transitions like descending or ascending stairs, stepping in and out of a tub, stooping, or reaching from one surface to another.